The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1155/2010/806538
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Hypertension in Diabetes: Does PPARγHave a Regulatory Role?

Abstract: Dysfunction of macro- and microvessels is a major cause of morbidity and mortality in patients with cardio-renovascular diseases such as atherosclerosis, hypertension, and diabetes. Renal failure and impairment of renal function due to vasoconstriction of the glomerular arteriole in diabetic nephropathy leads to renal volume retention and increase in plasma homocysteine level. Homocysteine, which is a nonprotein amino acid, at elevated levels is an independent cardio-renovascular risk factor. Homocysteine indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 107 publications
(132 reference statements)
1
24
0
Order By: Relevance
“…This finding might be suggestive of diastolic dysfunction, probably by the HcyT effect of increased endothelial-myocyte uncoupling, resulting in hypertension 39 . E/A ratio was increased in the Hcy group compared to the CB 6 group.…”
Section: Discussionmentioning
confidence: 96%
“…This finding might be suggestive of diastolic dysfunction, probably by the HcyT effect of increased endothelial-myocyte uncoupling, resulting in hypertension 39 . E/A ratio was increased in the Hcy group compared to the CB 6 group.…”
Section: Discussionmentioning
confidence: 96%
“…The present study has also shown the positive correlation between serum homocysteine and total cholesterol, Triglyceride, LDL cholesterol & negative correlation between serum homocysteine and HDL cholesterol in hypertensive subjects. Hyperhomocysteinemia, through its oxidative effects could reduce vasodilators like nitric oxide as well as promote extracellular matrix accumulation and smooth muscle cell proliferation, leading to vascular constriction and stiffness 36,37 . The atherogenicity of homocysteine may involve several mechanisms including LDLcholesterol oxidative modification, and HDL-cholesterol decrease 38 .…”
Section: Discussionmentioning
confidence: 99%
“…13,14 It has been proposed that hyperhomocysteinemia induces oxidative injury of vascular endothelial cells, arteriolar constriction, renal dysfunction, and increased sodium reabsorption. [15][16][17] Results of 2 meta-analyses suggest that the MTHFR C677T polymorphism is associated with an increased risk of hypertension, at least in Asian and white populations. 18,19 Our group previously found that the 677TT genotype is associated with a reduced risk of preeclampsia in Maya-Mestizo women.…”
Section: Circ Cardiovasc Genetmentioning
confidence: 99%